Morphomolecular study on the flat-faced longhorn beetle Batocera rufomaculata (De Geer, 1775) from Rehla, Palamu, Jharkhand, India - Kumar MANOJ; Ranjan RAKESH; Kumari NEHA; Singh R. BHARTI; Prasad S. MANORANJAN (Notulae Scientia Biologicae)
Batocera rufomaculata, often known as the ‘mango stem borer’ or ‘fig borer,’ is a serious pest of fig, mango, guava, jackfruit, pomegranate, and walnut in many parts of the world. Its infestations can result in reduced yields and even tree mortality. The larvae, which dig into the tree’s sub-cortex before moving deeper into the tree, cause the most harm. Continuous tunnelling weakens the wood, causing branches to break or the main stem to fall. Adults munch on green growth tips and twig bark. Their dispersion pattern and adaptability must be properly understood in order to regulate them. This study expands distributional pattern of B. rufomaculata found during a routine field survey in the Rehla region in the Palamu district of Jharkhand State, India. Morphological features have been described coupled with the isolation, amplification and sequencing of Mitochondrially encoded cytochrome C oxidase, subunit 1 gene, and its analysis based on BLASTn search. Accession id LC820410 of 643 bp long nucleotide sequence of CO1 has been presented. Distance matrix and phylogenetic tree were constructed using MEGA X software to establish intra-species and inter-species phylogeny and to get pairwise genetic-differences among the selected 20 strains species of genus Batocera including species Rufomaculata, Rufus, Celebiana, and Lineolata.